Standardization of In-vivo Nitrate Reductase Activity in Albizia lebbeck, Acacia nilotica and Dalbergia sissoo - Pokhriyal, T. C.; Raturi, A. S.; Nautiyal, H. O.; Joshi, S. R. (Indian Forester, 1988)
No abstract